2017
DOI: 10.1002/chem.201702039
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Multi‐Photon Absorption Materials: Beyond the Telecommunication Wavelength Band

Abstract: Very large molecular two- and three-photon absorption cross-sections are achieved by appending ligated bis(diphosphine)ruthenium units to oligo(p-phenyleneethynylene) (OPE)-based "stars" with arms up to 7 phenyleneethynylene (PE) units in length. Extremely large three- and four-photon absorption cross-sections, through the telecommunications wavelengths range and beyond, are obtained for these complexes upon optimizing OPE length and the ruthenium-coordinated peripheral ligand. Multi-photon absorption (MPA) cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The maximal values of the two‐photon absorption cross‐section ( σ 2 ), the real component of the cubic nonlinearity γ real , and the imaginary component of the cubic nonlinearity γ imag for the complexes are collected in Table ; the experimental spectral dependence data are presented in Figures S12–S45. We examined the intensity dependence of the open‐aperture Z‐scan traces at longer wavelengths and confirmed that where measurable n PA ( n ‐photon absorption) activity exists, it is 2PA in nature, in contrast to the 3PA and 4PA exhibited by the aforementioned stars and dendrimers …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The maximal values of the two‐photon absorption cross‐section ( σ 2 ), the real component of the cubic nonlinearity γ real , and the imaginary component of the cubic nonlinearity γ imag for the complexes are collected in Table ; the experimental spectral dependence data are presented in Figures S12–S45. We examined the intensity dependence of the open‐aperture Z‐scan traces at longer wavelengths and confirmed that where measurable n PA ( n ‐photon absorption) activity exists, it is 2PA in nature, in contrast to the 3PA and 4PA exhibited by the aforementioned stars and dendrimers …”
Section: Resultsmentioning
confidence: 96%
“…Metal-alkynyl complexesh ave also attracteda ttention as potentialc ubic NLO-activem aterials, with the focus largely on complexes with extended p systemss uch as cruciforms, [9] stars, [10] oligomers, [11] and dendrimers, [12] and with examples displaying record values of multiphoton absorption cross-sections. [13] The nonlinear refraction and nonlineara bsorption coefficients are strongly wavelength dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cubic optical nonlinearities of the H‐shaped complexes were assessed by the Z‐scan technique over the range 500–1600 nm and employing 130 fs light pulses. Two‐photon absorption cross‐sections for the distorted‐H‐shaped complexes in the present study are large (up to 5500 GM at 880 nm), while one example displays significant three‐photon absorption (1200×10 −80 cm 6 s 2 at 1300 nm); complex 6 b is amongst the best molecular materials assessed under fs conditions thus far ,,,…”
Section: Resultsmentioning
confidence: 99%
“…10 Despite this promising result, wavelength-dependence studies of the nonlinear optical (NLO) properties of AuNP hybrids across the visible and near-infrared (NIR) regimes are scarce, the only example (to the best of our knowledge) being a spectral dependence study of AuNPcaptopril hybrids over the range 550-1100 nm (maximal 2PA cross-section 25,000 GM at 550 nm, determined by fs Z-scan; captopril = (2S)-1-[(2S)-2-methyl-3sulfanylpropanoyl]pyrrolidine-2-carboxylic acid). 9 Dendrimers, rods, and stars (zero-generation dendrimers) containing trans-[Ru(C2R)X(dppe)2] units (X = Cl, C2R`; dppe = 1,2-bis(diphenylphosphino)ethane) display much greater multi-photon absorption (MPA) activity than their purely organic analogues, [19][20][21][22] with strong 2PA, three-photon absorption and (in some cases) four-photon absorption in the NIR region; intense metal-to-ligand charge-transfer (MLCT) in the visible region and dπ-pπ orbital overlap between the ruthenium and the alkynyl ligands are key contributors to the outstanding NLO merit of these organometallic complexes. 23,24 AuNP-organometallic dendrimer hybrids have shown promise for applications in catalysis, 25,26 sensing, 27,28 and energy storage, 27 but there are thus far no studies of the NLO properties of AuNP-organometallic dendrimer hybrids, particularly 2PA spectral-dependency studies, despite the abovementioned strong MPA performance of organometallic dendrimers/stars and the significant improvement in NLA that can accrue from coupling molecular materials to AuNPs.…”
mentioning
confidence: 99%